Emprego do Webmapping como ferramenta de gestão - aplicação na área urbana de Jaguari (RS) - Prina, Bruno Zucuni (2019)
Among natural disasters, floods are characterized like the event with greater incidence on urban organizational systems, propagating a series of problems to the population. Thus, it is justified to carry out this paper according to the importance to unify the issues of mapping flooded areas in relation to the availability and organization of cartographic data in computerized media (using WebMappings). Thus the population will have at disposal real information about the problems of the floods in their living space, contributing to planning actions on disruptive events. Thus, the central point of analysis of this research refers to the discussion about the advantages associated with the use of WebMappings and how much this tool assists in flood risk management. In addition, there is still the specific goal of developing online maps of the urban floods of Jaguari, through the structuring of data and metadata, following suggested INDE / CONCAR instructions. For this, it is necessary to perform the theoretical description of concepts related to the subject of study, with focus on WebMappings. Still, it can be emphasized that there was the organization of the data and metadata of the geographic archives; the creation of an online platform with WebMappings; the compilation of the standard methodology that gave rise to the mapping of risk areas; and finally, there was the evaluation of the website developed, with the purpose of highlighting their deficiencies and, from this, improve its structure, in addition to contextualize questions of the advantages associated with the use of WebMappings. Among the results obtained, the importance of structuring the information plans to compose the informative structure of online maps is emphasized. Another important point is about the results obtained with the evaluation of the website, since a number of improvements can be made in relation to its information structure, along with the indexing of specific analyzes on the importance of online maps. From this, we highlight that the dynamics of performing the geographic data exposure along the internet has proved to be a routine that runs a lot of simplicity in the analysis of a certain mapping theme. For this reason, WebMappings are growing, propagating a high tendency to become effective as a new way of "making geography". Access to information, quickly and accurately, is one of the great advantages of WebMappings, consolidating itself as an instrument linked to the management of problems related to the human being, mainly from urban floods.